Child abuse, a case report (Medical Journal of Indonesia, 2004)
Child abuse is a pervasive social and medical problem that remains a major cause of disability and death among children. The annual incidence of abuse is estimated to be 15 to 42 cases per 1,000 children and appears to be increasing. Fractures are the second most common presentation of physical abuse after skin lesions, and approximately one third of abused children will eventually be seen by an orthopedic surgeon. We report a 7-month-old boy who was suspected to be abused. Our diagnosis was based on findings of multiple fractures, delay in seeking medical treatment and discrepancy between the history of illness and the clinical findings. He sustained multiple fractures in variety of healing, namely fractures on left supracondylar humeri, left radius and ulna, right radius and ulna, both femora, right tibia, and left tibia and fibula. Radiological examination was an important modality in revealing the possibility of abuse on this child. He had received medical treatment, protection, consultation team for the parents and an underway police investigation. (Med J Indones 2004; 13: 59-65) Keywords: child, abuse